A bibliometric analysis of the scientific production of E-learning in higher education (1998-2020) - Gao, Yanjun; Wong, Su Luan; Md. Khambari, Mas Nida; Noordin, Nooreen (International Association of Computer Science and Information Technology, 2022)
Studies on E-learning in higher education have been gaining increasing attention from scholars in recent years. To have an overall understanding of these scientific productions of E-learning, a bibliometric analysis was done to conduct a quantitative scientific analysis of 1985 journal articles collected from the Scopus database. All the documents were analyzed through Biblioshiny and VOSviewer software. The results revealed that publications on E-learning increased at an exponential speed with a 26.48% annual growth rate. The International Journal of Emerging Technologies in Learning was the most productive while Computer and Education was considered the most impactful journal based on total citations. Europe and the United States played the leading role by publication quantity and total citations. At the researcher level, Al-samarraie, H. was ranked the top author in terms of both productivity and h-index, while Ebner, M. was the most influential author by total citations. The main themes drawn from the cluster analysis were “distance learning”, “technology acceptance”, “teachers’ professional training and development” and “quality assessment of E-learning”, which confirmed further previous research themes. The limitations of the study and recommendations for future research conclude the paper.